International law on the left re-examining Marxist legacies - Marks, Susan (Cambridge University Press, 2008)
Against expectations that the turn away from state socialism would likewise initiate a turn away from Marxist thought, recent years have seen a resurgence of interest in Marxism and its reassessment by a new generation of theorists. This book pursues that interest with specific reference to international law. It presents a sustained and fascinating exploration of the pertinence of Marxist ideas, concepts and analytical practices for international legal enquiry from a range of angles. Essays consider the relationship between Marxism and critical approaches to international law, the legacy of Soviet international legal theory, the bearing of Marxism for the analysis of international trade law and human rights, and the significance for international legal enquiry of such Marxist concepts as the commodity, praxis and exploitation